Rho-Rho Loran-C Combined with Satellite Navigation for Offshore Surveys - Grant, S. T. (The International Hydrographic Review, 2015)
The Loran-C system of navigation recently became usable in the rho-rho (range-range) mode with the installation of atomic clocks at all the Loran-C stations. This paper outlines briefly the principles of rho-rho Loran-C operation and the associated problems of geodesy and radio wave propagation. It describes the procedure for using rho-rho Loran-C alone and in combination with Satellite Navigation, as developed over the past two years at the Bedford Institute of Oceanography. Results of accuracy tests are given along with estimates of the magnitudes of the various sources of errors in Loran-C range measurements for both the standalone and satellite aided modes of operation. The results generally show a 2 σ \!\, absolute ranging accuracy of 270 m using rho-rho Loran-C alone with an improvement to about 180 m when combined with Satellite Navigation. The Bedford Institute of Oceanography rho-rho Loran-C system has been used routinely with Satellite Navigation at ranges of 2 500 km (1 250 n.m.). Based on this experience the rho-rho Loran-C coverage would include most of the North Atlantic Ocean and large areas o f the Pacific.